Energy Expenditure Estimation During Crutch-Orthosis-Assisted Gait of a Spinal-Cord-Injured Subject - Michaud, Florian; Mouzo, Francisco; Lugrís, Urbano; Cuadrado, Javier (Frontiers in Neurorobotics, 2019)
Determination of muscle energy expenditure by computer modeling and analysis is of great interest to estimate the whole body energy consumption, while avoiding the complex character of in vivo experimental measurements for some subjects or activities. In previous papers, the authors presented optimization methods for estimating muscle forces in spinal-cord-injured (SCI) subjects performing crutch-assisted gait. Starting from those results, this work addresses the estimation of the whole body energy consumption of a SCI subject during crutch-assisted gait using the models of human muscle energy expenditure proposed by Umberger and Bhargava. First, the two methods were applied to the gait of a healthy subject and experimentally validated by means of a portable gas analyser in several 5-minute tests. Then, both methods were used for a SCI subject during crutch-assisted gait wearing either a passive or an active knee-ankle foot orthosis (KAFO), in order to compare the energetic efficiency of both gait-assistive devices. The SCI subject presented improvements of the gait pattern and reduced his energy consumption by using the actuated gait device. Computer modeling and analysis can help to design new gait devices, thus increasing the chances of walking for these population along with the associated benefits for their health.